2003
DOI: 10.1152/ajprenal.00328.2002
|View full text |Cite
|
Sign up to set email alerts
|

Moderate alcohol intake has no impact on acute and chronic progressive anti-thy1 glomerulonephritis

Abstract: Moderate alcohol consumption has shown beneficial effects in experimental and human cardiovascular disease. With the use of rat models of acute and chronic progressive anti-thy1 glomerulonephritis (GN), we tested the hypothesis that moderate alcohol intake is protective in renal fibrotic disease. In acute anti-thy1 GN, untreated nephritic rats showed marked mesangial cell lysis and induced nitric oxide production at day 1 and high proteinuria, glomerular matrix accumulation, and transforming growth factor (TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Together, these findings indicate that the long-term ethanol consumption alters hydric balance [6], which could be partially reversed by withdrawal. It was shown that moderate ethanol consumption for 15 weeks does not change matrix protein production in glomerulofibrosis [29], but heavy ethanol consumption for 6 and 12 weeks induced tubular necrosis [16] and hypertrophy and degeneration of the epithelia of the renal tubules [15]. Our results further extend those previous studies by showing that 24 weeks of ethanol consumption causes atrophy of renal corpuscles and glomeruli and reduces the volume density of glomeruli without changing their areal density, which indicates that it does not lead to a marked loss of glomeruli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these findings indicate that the long-term ethanol consumption alters hydric balance [6], which could be partially reversed by withdrawal. It was shown that moderate ethanol consumption for 15 weeks does not change matrix protein production in glomerulofibrosis [29], but heavy ethanol consumption for 6 and 12 weeks induced tubular necrosis [16] and hypertrophy and degeneration of the epithelia of the renal tubules [15]. Our results further extend those previous studies by showing that 24 weeks of ethanol consumption causes atrophy of renal corpuscles and glomeruli and reduces the volume density of glomeruli without changing their areal density, which indicates that it does not lead to a marked loss of glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is evidence that the pathological activation of the intrarenal RAS enhances oxidative stress [2, 27, 28] and promotes kidney injury, namely of glomeruli, tubules and vasculature [22, 24, 28]. Data regarding the effects of ethanol consumption on kidney structure and function is divergent, probably due to differences in the amount of ethanol consumed in the several studies [6, 15-17, 29]. It is possible that, alongside the systemic hypertensive effects, heavy ethanol consumption may also impair kidney structure and function, therefore contributing to the maintenance of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Red and white blood cell counts were determined in an automated cell counter (XE 2,100, Sysmex, Norderstedt, Germany) using a standard fluorescent flow cytometry technology (15). Plasma and urine creatinine and plasma urea were measured spectrometrically in enzyme-based assays (16). The glomerular filtration rate was calculated on the basis of serum and urinary creatinine concentrations and the corresponding urine volume and is expressed as milliliters per minute per 100 grams body wt.…”
Section: Methodsmentioning
confidence: 99%
“…Glomeruli from individual rats were isolated by a graded sieving technique (160-, 125-, and 71-m mesh metal sieves), as described previously (17). For cultures of renal cortical tissue, a piece of cortical tissue was weighed and minced extensively with a razor blade (16). Glomeruli or cortical tissues were suspended in DMEM supplemented with 0.1 U/ml insulin, 100 U/ml penicillin, and 100 g/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…To test this hypothesis, rats with anti-thy 1-induced chronic progressive glomerulosclerosis were treated with the novel lymphocyte-specific immunosuppressant FTY720. Antithy 1-induced chronic glomerulosclerosis is produced immunologically by injection of anti-thy 1 antibodies into uninephrectomized rats, leading to a short-term complement-and nitric oxide-mediated acute glomerulonephritis [17,18]. Afterwards, the disease progresses autonomously toward glomerulosclerosis, tubulointerstitial fibrosis, and renal insufficiency over months in a not primarily immune-mediated manner.…”
mentioning
confidence: 99%